Multilobular Tumor of Bone in Bitches: Clinical, Histopathological, Immunohistochemical and Overall Survival Aspects - Benvenuto Baldasso, Adônis; Eunice Lavalle, Gleidice; Monteiro de Castro Cunha, Rúbia; Antônio Carneiro, Rubens; Pierezan, Felipe; Teixeira, Stéfane Valgas; Baracat de Araújo, Roberto (Acta Scientiae Veterinariae, 2023)
Background: Multilobular tumor of bone (MTB) is an unusual neoplasm with variable biologic behavior which originates primarily in bone tissues. Radiographs computed tomography (CT), and magnetic resonance imaging (MRI) are useful in diagnoses and surgical planning. Tumor removal with wide surgical margins is the treatment of choice. Immunohistochemistry has been shown as an important tool in veterinary oncology to define therapeutic and prognostic decisions. The goal of this study was to report 2 distinct cases of multilobular tumor of bone, their Cox-2 and Mib-1 immunohistochemical profile and its impact on overall survival. Case: Two bitches were presented at the Oncology Department of the Veterinary Hospital in the Veterinary School of Universidade Federal de Minas Gerais (UFMG). Both had a history of a progressive, painless, circumscribed, and firm facial mass. The 1st patient was a 8-year-old intact bitch mixed breed, weighing 50 kg, that presented a fast growing right infraorbital 3-cm mass, causing eye displacement. The 2nd patient was a 7-year-old spayed bitch Labrador retriever, weighing 28 kg, that presented a left temporal 8-cm mass. Neurologic examination of both bitches was normal. Skin over the nodules was strained, but with no ulceration. Radiographic exams of the head revealed lytic and proliferative bone reaction, with loss of cortical definition in both cases. These alterations were seen on the left zygomatic arch of the retrobulbar region, involving part of the mandible and of the nasal sinus lateral frontal bone in 1st patient, and on the right temporal process of the zygomatic bone in 2nd patient. The last one, also showed a granular solid mass with little contact with skull bones. Complete blood count, biochemistry profile, electrocardiogram, and 3-view thoracic radiographs were performed. Results were within normal ranges for the species and no signs of metastasis was seen on the radiographs. Location, size, and density of the mass, adjacent tissue compression, absence of cranial invasion, and lymph node size were rigorously evaluated with CT, allowing an individualized surgical planning to achieve complete mass removal and maintenance of the function of adjacent structures. Both animals were submitted to surgery. Both tumors were fixed on 10% neutral buffered formalin and sent to the Animal Pathology Department of UFMG for histopathological examination and margin assessment. Both tumors were diagnosed as grade I MTB. Tumor immunohistochemistry was performed to identify prognostic factors that could be used to better define therapeutic treatments and to try to clarify the discrepancy in disease progression between both tumors. The 1st patient expressed 20% of Mib-1 and was considered score 2 of Cox-2. The 2nd one expressed 5% of Mib-1 and was considered score 1 of Cox-2. Considering the diagnoses and histological characteristics of the tumors, it was decided for clinical follow-up of patients without additional therapeutic complementation. Even considering incomplete surgical margins in 2nd patient, adjuvant chemotherapy was not performed, due to low mitotic index and low histological grade. The 1st patient had an overall survival of 240 days, and death was due to recurrence and disease progression; and the 2nd did not show recurrence nor metastasis after 1200 days. Discussion: Proper and individualized surgical planning and histopathological evaluation are extremely important to guide treatment decisions. However, immunohistochemistry can be important in MTB cases, to help define which patients should be submitted to surgery alone and which patients could be benefited from adjuvant chemotherapy. Keywords: MTB, Cox-2 and Mib-1 profile, neoplasm, tumor, oncology, canine, dog, bone tissues.